Hubungan Antara Keharmonisan Keluarga Dengan Konsep Diri Siswa SMA Kristen Citra Bangsa Kupang - Rihi, Diana Novita; Upa, Muhammad Pua; Nalle, Andriani P; Febriana, Febriana (Prodi Bimbingan Konseling FKIP UNDANA, 2023)
This study aims to investigation of family harmony, students' self-concept, and the relationship between family harmony and the self-concept of class X SMA K Christian Citra Bangsa Kupang. This study uses a quantitative approach with a descriptive correlational research type. This study was conducted at Citra Bangsa Christian High School, Kupang City with a population of 173 students. The sampling technique used was proportional random sampling technique and a total of sample 78 students. The data collection technique uses Instrument with a Likert scale model. The data analysis techniques used are descriptive analysis and correlational analysis with the SPSS for Windows 16.00 Version program. The study results show that (1) dominant family harmony is in the low category with a percentage of 39% (31 people) (2) Dominant self-concept is in the low category with a percentage of 35% (28 people). Product moment correlation analysis shows that family harmony and self-concept have a significant and positive relationship with a calculated r value of 0.702 (r calculated 0.701 > r table 0.227). Based on the research results, it is known that there is a significant and positive relationship between family harmony and the self-concept of class X students at Citra Bangsa Christian High School, Kupang. The results of this study indicate that the lower family harmony, the lower the self-concept of class X students at Citra Bangsa Christian High School Kupang.